If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 5y + -7 = 0 Reorder the terms: -7 + -3x + 5y = 0 Solving -7 + -3x + 5y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + -3x + 7 + 5y = 0 + 7 Reorder the terms: -7 + 7 + -3x + 5y = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -3x + 5y = 0 + 7 -3x + 5y = 0 + 7 Combine like terms: 0 + 7 = 7 -3x + 5y = 7 Add '-5y' to each side of the equation. -3x + 5y + -5y = 7 + -5y Combine like terms: 5y + -5y = 0 -3x + 0 = 7 + -5y -3x = 7 + -5y Divide each side by '-3'. x = -2.333333333 + 1.666666667y Simplifying x = -2.333333333 + 1.666666667y
| 8(1.5+.5y)-4y=12 | | 5-2(x+5)=40 | | 4x(126)= | | 20-5s=8 | | x^2(x-3)(x^2-9)(x^2+4)=0 | | W=Fa+FB | | 6x^2(36)= | | x^2+18x+y^2=-17 | | (4x+3)-5=5(x+4) | | x*12+-42+85=246 | | 74=10+4x | | 5y-7+y+27=5y+20-3y | | 7(0)-2(6)=12 | | x^2+y^2+18x+17=0 | | x(x)=16316 | | 190=-8+9x | | 8x-14=-16 | | 7(5x+8)=-x+4 | | 0.10(y-9)+0.12y=0.18y-0.07(10) | | 7(5x+8)=-x+4 | | 8(2x+1)=7x+7 | | 4-9=6+x | | 4-9=6+x | | 4-9=6+x | | x-47=28 | | 4x^3(6)= | | 4=x/2+8 | | 32-4(9-2)=4(T-1) | | -81=-4x+3 | | X+1(4x-2)=2x-1(3x-1) | | 20-3z=7z+8 | | x/10+6=8 |